At the crossroads of oral health inequities and precision public health. (7th May 2019) - Gansky, Stuart A.; Shafik, Sarah
Abstract: Objectives: This paper reviews the precision public health literature pertaining to oral health, identifies possible threats that could inadvertently increase health inequities, and proposes potential opportunities that precision public health could utilize to reduce oral health inequities. Methods: The health sciences literature was reviewed and supplemented with new data to identify important issues relating to precision medicine, precision oral health, precision public health, and health equity. Results: Examples from general health and oral health were provided to illustrate salient concepts. Conclusions: Future precision public health should utilize multifactorial, multi‐level conceptual frameworks and conceptual causal models with upstream social determinants and downstream health effects, as well as a proportionate universalism perspective; and proper analytic methods, including sufficient sample sizes, appropriate statistical competitors, health disparity indices, causal modeling, and internal and external validation.